Inhalable and respirable dust metal concentration in existing and construction stage of airport infrastructure - Mohd. Din, Shamzani Affendy; Nik Yahya, Nik Nurul Hidayah; Othman, Rashidi (American Scientific Publishers, 2017)
With the explosion due to shipment of Lithium-ion battery that causes the loss of MH370 issue raised in 2015, the aviation stakeholders begin to pay attention towards the metal compound to exist in and surrounding the flights and airport. This research supports this issue by critically analyzed the metal concentration found at the existing international airport and the construction of the nearby international airport, hence suggesting comprehensive result towards the fundamental knowledge to this giant intelligent infrastructure. The personal airborne particles sampling were done between two classification size of airborne particles that were respirable and inhalable dust. The metal content tested by using the ICPMS was done to determine the amount of concentration of Ba, Cr,Cu, Fe, Mn, Ni, Pb, V and Zn. Comparison between two types of built environment for an airport infrastructure is found through this analysis. This study also further showed that metals concentration level varies between the respirable and inhalable dust. The mean ranges of respirable dust found in the airport and its construction site are between 0.0575 and 72.413 mg mg−3. Lower ranges in inhalable dust are found between 0.048 and 55.190 mg m−3. Thus, sum up to an overall average for all metal concentrations at 36.235 and 27.619 mg m−3, for respirable and inhalable dust, accordingly. The dominant metals for all sampling locations in airports are Fe, Zn, and Ni. The highest is iron for both inhalable dust and respirable dust at average readings of 72.413 and 55.190 mg m−3, correspondingly. Hence, suggesting the amount of respirable to inhalable dust are exceed at 13.49 per cent. Thus, amount to the ratio of respirable towards inhalable dust at 56.74 per cent. These results indicate that as the above chemical content reaching alveolar region, it brings hazard to the human health. It is to be highlighted that the average ratio of respirable towards inhalable dust for existing building in operations are slightly higher than the fraction found at the construction site of an airport at 0.16 per cent. Thus, indicating that human presence influenced more towards the respirable dust dissemination in an environment.